Optimizing the Lexical Approach to Develop EFL Learners’ Collocational Accuracy and the Acquisition of the Idiom Principle in Writing : The Case of First Year University Students - DEBABI, Mohammed (Université de Mostaganem, 2020)
The habitual co-occurrence of two or more items in language is technically termed as collocation. The pervasiveness of collocations in native speakers‟ use of language has highlighted their vital importance in achieving native-like fluency. Any underuse, overuse or misuse of collocations is viewed as a common source of inaccuracy and foreign sounding chiefly in one' writing. To say the least, knowledge of how words combine appropriately has often been a missing part in many EFL classes in Algeria. To this end, the present study aims to assess the extent to which the use of the Lexical Approach can help Algerian EFL intermediate learners improve their collocational accuracy and, in turn, operate on the Idiom Principle in their writing. To carry out this research, we recruited a sample of 62 first year university students at the Department of English in Chedli Benjdid University of El Tarf, Algeria. Those EFL majors were assigned to an experimental group and a control group. The former was taught collocations explicitly through the Observe Hypothesis Experiment (OHE) practices of the Lexical Approach, while the latter was taught with no focus on collocations. To gather the required data, three tools were used: a questionnaire was administered in order to identify the participants' pre-existing awareness of collocations, pre and post-tests were given to measure the participants' receptive and productive collocational knowledge and, lastly, an interview was conducted to explore the skills that the subjects have acquired to process collocations. Analysis of the findings indicates that there is a correlation between training the participants to chunk language successfully and the increase of collocational strength with high mutual information (MI) scores in those participants‟ writing. Besides, the results of the current study confirmed that a period of five months of adopting the OHE practices inside the classroom has proven to be effective in developing EFL intermediate learners‟ collocational competence .The latter reflects a considerable increase in collocational accuracy which, in turn, proved to correlate with learners‟ acquisition of the ability to operate on the Idiom Principle. In the light of those findings, the present study presents a number of pedagogical implications as it also highlights certain issues for related future research.
Keywords: collocational accuracy, high-strength collocations, Idiom Principle, Lexical Approach, OHE practices